Paraphrasing as a Strategy to Develop Reading Comprehension at The Tertiary Level of Education - Nivedita Malini Barua (Pascasarjana Universitas Negeri Makassar, 2021)
The three aims of this study are to determine (1) the reading proficiency and the motivation level of a group of tertiary level learners, (2) how far paraphrasing as a strategy can help in developing the reading comprehension of the learners, and (3) whether this strategy also motivates the learners to read more. This study employed a quasi-experimental design. The research population comprised all 18 students in the third semester of the MA in ELT (English Language Teaching) programme of Gauhati University. The data were collected by using (1) two types of tests to measure abilities in literal and inferential comprehension, (2) paraphrasing as technique for reading and (3) questionnaires. The results showed that there was a greater engagement with the text and higher levels of motivation while using the paraphrasing strategy. However, more research needs to be carried out to obtain conclusive evidence that the reading comprehension of students can be developed substantially with the use of the paraphrasing strategy.